The brass verdict - Connelly, Michael, 1956-; Giles, Peter (New York, NY : Hachette Audio, 2008)
Just as defense attorney Mickey Haller's life is returning to normal, a Hollywood lawyer named Jerry Vincent is murdered and Mickey takes on the case of the accused, which could take his career into the big leagues. Haller learns that the killer may be looking for him and Harry Bosch. With danger mounting, Bosch and Haller decide to work together.
Abridged audio version of the book.
In container (15 cm.).
Compact discs.
Read by Peter Giles.
Keywords: Bosch, Harry -- Fiction; Haller, Mickey (Fictitious character) -- Fiction; Police -- California -- Los Angeles -- Fiction; Lawyers -- Crimes against -- Fiction; Murder -- Investigation -- Fiction; Los Angeles (Calif.) -- Fiction; Audiobooks